Hydrothermal synthesis and characterisation of tin doped ZnO polyscale crystals with hexylamine additive - T. Parvin (2018)
Polyscale crystalline ZnO particles doped with tin were synthesised under mild hydrothermal conditions (T, 150°C; P, autogeneous; experimental duration, 16 h) in the presence of hexylamine as an additive. The resultant products synthesised were characterised using powder X-ray diffraction, Fourier transform infrared, scanning electron microscopy, measurement of zeta potential and dynamic light scattering. The characterisation results indicated better morphology, particle size distribution and low agglomeration of the polyscale crystals synthesised in the presence of hexylamine additive. The photodegradation of brilliant blue dye using these metal oxide polyscale crystals was investigated under sun light and ultraviolet irradiation. The degradation of the dye was checked using the following parameters: chemical oxygen demand and percentage transmission (%T). The photodegradation results showed that the tin doped ZnO polyscale crystals with hexylamine additive had higher efficiency compared to the reagent grade ZnO in photodegradation of brilliant blue dye. © 2012 W. S. Maney & Son Ltd.